Human Capital: A Bibliometric Analysis of Research Evolution - Loso Judijanto; Paramita Andiani; Ilham Akbar Bunyamin (West Science Journal Economic and Entrepreneurship, 2026)
Human capital has become a fundamental concept in explaining economic development, organizational competitiveness, innovation capability, and sustainable growth. However, the evolution of research themes, intellectual structures, and emerging directions within human capital studies remains fragmented across different disciplines. This study aims to examine the development and research landscape of human capital through a bibliometric analysis approach. Data were collected from the Scopus database using relevant search terms related to human capital, and the retrieved publications were analyzed using bibliometric techniques, including performance analysis, citation analysis, co-authorship analysis, keyword co-occurrence analysis, and thematic evolution mapping. The findings reveal that human capital research has experienced significant growth and has developed into a multidisciplinary field involving economics, management, entrepreneurship, education, innovation, and sustainability. The citation analysis identifies influential studies focusing on entrepreneurship, psychological capital, strategic management, and sustainable competitive advantage, while the keyword analysis demonstrates a transition from traditional themes such as education, employment, and productivity toward emerging themes including innovation, intellectual capital, social capital, and sustainable development. Furthermore, collaboration analysis highlights the dominant contribution of institutions and countries from North America, Europe, and Asia in shaping global human capital research. This study contributes to the literature by providing a comprehensive understanding of the intellectual evolution of human capital research and identifying future research opportunities related to digital capabilities, green human capital, and adaptive workforce development.